Pengukuran Kinerja Sistem E-Learning UNITOMO Menggunakan Framework ITIL V4 - Zisti Shinta Maharrani; Lambang Probo Sumirat; Yudi Kristyawan (Progresif: Jurnal Ilmiah Komputer, 2024)
The E-Learning System of Dr. Soetomo University in Surabaya provides academic services for hybrid learning, also known as E-Learning. This system has been running for a long time and has received many complaints from users, such as server downtime during exams, repeated material uploads, and service management issues. To support operational and incident management, an evaluation is needed to ensure the system runs smoothly and to determine the optimal quality of service. This study focuses on the ITIL V4 framework tailored to the needs and conditions by utilizing practices such as Incident Management, Monitoring and Event Management, Service Continuity Management, Service Desk Management, and Service Request Management. An analysis is conducted by distributing questionnaires to directly involved users, including lecturers, students, heads of study programs, and academic affairs sub-department heads. Based on the calculation results, the maturity level of the Unitomo E-Learning System is still at level 3 (Defined) with a score of 3.37. Recommendations include improving documentation, standardizing the assessment of system service quality, and providing good user training and support to enhance performance.Keywords: E-Learning; Information Technology Infrastructure Library V4 Framework; Service Evaluation AbstrakSistem E-Learning Universitas Dr. Soetomo Surabaya memiliki pelayanan akademik untuk pembelajaran hybrid atau disebut E-Learning. Sistem ini telah berjalan lama dan banyak keluhan yang diterima pengguna seperti permasalahan server down saat ujian, upload materi berulang, dan manajemen layanan. Untuk mendukung operasional sekaligus pengelolaan insiden layanan IT diperlukan evaluasi yang bertujuan memastikan sistem berjalan baik dan mengetahui kualitas layanan berjalan optimal. Dalam penelitian ini berfokus pada framework ITIL V4 menyesuiakan kebutuhan dan kondisi dengan menggunakan praktik Incident Management, Monitoring and Event Management, Service Continuity Management, Service Desk Managament, dan Service Request Management. Analisa dilakukan dengan menyebarkan kuesioner kepada pengguna yang terlibat langsung dalam pengguna, yaitu Dosen, Mahasiswa, Kaprodi dan Kasubbag TU Akademik. Berdasarkan hasil perhitungan maturity level sistem E-Learning Unitomo masih berada di level 3 (Defined) dengan nilai 3.37. Rekomendasi yang dapat diberikan berupa peningkatan pendokumentasian, standarisasi penilaian kualitas layanan sistem, serta penyediaan pelatihan dan dukungan pengguna yang baik untuk meningkatkan kinerja.Kata kunci: E-Learning; Framework Infrastructure Technology Information Library V4; Evaluasi Layanan